2010
DOI: 10.1063/1.3456386
|View full text |Cite
|
Sign up to set email alerts
|

InAs/GaSb type-II superlattice structures and photodiodes grown by metalorganic chemical vapor deposition

Abstract: We report on the characterization and performance of epitaxial structures and photodiodes based on InAs/GaSb type-II superlattices grown by metalorganic chemical vapor deposition. Interfacial layers were introduced at the superlattice interfaces to compensate the tensile strain and hence to improve the overall material quality of the superlattice structures. The optimal morphology and low strain was achieved via a combined interfacial layer scheme with InAsSb+InGaSb layers. Using this scheme, a p-i-n photodiod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…Additionally, a rougher starting surface has been associated with increased decomposition of metastable layers. [16][17][18][19] Studies that do exist have reported high densities of mesoscopic defects, often pyramidal in shape, 20,21 at typical densities of 10 4 to 10 5 cm À2 . 15 However, there are a lack of studies of the morphology of GaSb buffer layers grown by molecular beam epitaxy (MBE).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a rougher starting surface has been associated with increased decomposition of metastable layers. [16][17][18][19] Studies that do exist have reported high densities of mesoscopic defects, often pyramidal in shape, 20,21 at typical densities of 10 4 to 10 5 cm À2 . 15 However, there are a lack of studies of the morphology of GaSb buffer layers grown by molecular beam epitaxy (MBE).…”
Section: Introductionmentioning
confidence: 99%
“…There are few reports on the growth and characterization of MOCVD-grown InAs/GaSb T2SLs [18,19] as well as InAs/InAsSb T2SLs [15,20]. The authors have investigated the viability of short-period InAs/GaSb T2SL growth by MOCVD on GaAs and GaSb substrates [21,22] and have demonstrated an InAs/GaSb T2SL photodiode with a cut-off wavelength of l$8 mm [23,24]. The next step is to explore the feasibility of the T2SL photodiodes employing InAs/InAsSb SLs in comparison with InAs/GaSb T2SLs grown by MOCVD.…”
Section: Introductionmentioning
confidence: 96%
“…However, the growth of InAs/GaSb SLs with high crystalline quality and good optical properties by metalorganic chemical vapor deposition (MOCVD) remains a great challenge. The difficulties arise not only from the lattice mismatch between InAs and GaSb [9,10], but also from the special V-group precursor of trimethylantimony (TMSb) and interdiffusion near the interfaces where no common atoms exist. Previous report has shown the arsenic-for-antimony and indiumfor-gallium exchanges by using cross-sectional scanning tunneling microscopy [11].…”
Section: Introductionmentioning
confidence: 99%